2021
DOI: 10.1038/s41467-021-27462-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix remodeling through endocytosis and resurfacing of Tenascin-R

Abstract: The brain extracellular matrix (ECM) consists of extremely long-lived proteins that assemble around neurons and synapses, to stabilize them. The ECM is thought to change only rarely, in relation to neuronal plasticity, through ECM proteolysis and renewed protein synthesis. We report here an alternative ECM remodeling mechanism, based on the recycling of ECM molecules. Using multiple ECM labeling and imaging assays, from super-resolution optical imaging to nanoscale secondary ion mass spectrometry, both in cult… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 83 publications
2
40
0
Order By: Relevance
“…Considering that it appears to be largely synaptic and tightly linked to local activity, it is possible to imagine that this mechanism is intimately involved in synaptic function. In agreement with this claim, it was shown that perturbing TNR recycling with large antibody aggregates interfered severely with synaptic vesicle release and resulted in structural changes to the postsynapse (Dankovich et al, 2021). We predict that such perturbations to ECM recycling would also have implications for synaptic plasticity, both at the structural and the molecular level, and may also manifest in brain disorders.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Considering that it appears to be largely synaptic and tightly linked to local activity, it is possible to imagine that this mechanism is intimately involved in synaptic function. In agreement with this claim, it was shown that perturbing TNR recycling with large antibody aggregates interfered severely with synaptic vesicle release and resulted in structural changes to the postsynapse (Dankovich et al, 2021). We predict that such perturbations to ECM recycling would also have implications for synaptic plasticity, both at the structural and the molecular level, and may also manifest in brain disorders.…”
Section: Discussionsupporting
confidence: 72%
“…A novel mechanism of ECM remodeling was presented in a recent study by Dankovich and colleagues, based on the recycling of ECM molecules at the synapse. The authors proposed that these molecules are constitutively internalized into neurons, and subsequently resurface and re-integrate into the ECM around synapses (Dankovich et al, 2021 ). A complete recycling loop was described for the glycoprotein TNR, which spans ~3 days ( Figure 3 ).…”
Section: Recycling Of Synaptic Ecmmentioning
confidence: 99%
See 3 more Smart Citations